A quantitative serum biomarker of circulating collagen X effectively correlates with endochondral fracture healing. Issue 1 (20th July 2020) - Working, Zachary M.; Morris, Elizabeth R.; Chang, Jiun Chiun; Coghlan, Ryan F.; Johnstone, Brian; Miclau, Theodore; Horton, William A.; Bahney, Chelsea S.
Abstract: Currently, there are no standardized methods for quantitatively measuring fracture repair. Physicians rely on subjective physical examinations and qualitative evaluation of radiographs to detect mineralized tissue. Since most fractures heal indirectly through a cartilage intermediate, these tools are limited in their diagnostic utility of early repair. Prior to converting to the bone, cartilage undergoes hypertrophic maturation, characterized by the deposition of a provisional collagen X matrix. The objective of this study was to characterize the kinetics of a novel collagen X biomarker relative to other biological measurements of fracture healing using a murine model of endochondral fracture repair in which a closed, mid‐shaft tibia fracture was created using the classic drop‐weight technique. Serum was collected 5 to 42 days post‐fracture in male and female mice and compared to uninjured controls (n = 8‐12). Collagen X in the serum was quantified using a recently validated ELISA‐based bioassay ("Cxm") 1 and compared to genetic and histological markers of fracture healing and inflammation. We found the Cxm biomarker reliably increased from baseline to a statistically unique peak 14 days post‐fracture that then resolved to pre‐fracture levels by 3 weeks following injury. The shape and timing of the Cxm curve followed the genetic and histological expression of collagen X but did not show a strong correlation with local inflammatory states. Assessment of fracture healing progress is crucial to making correct and timely clinical decisions for patients. This Cxm bioassay represents a minimally invasive, inexpensive technique that could provide reliable information on the biology of the fracture to significantly improve clinical care.